Therapeutic options and postoperative wound complications after extremity soft tissue sarcoma resection and postoperative external beam radiotherapy - Abouarab, Mohamed H.; Henn, Dominic; Hirche, Christoph; Eweida, Ahmad; Uhl, Matthias; Kneser, Ulrich; Kremer, Thomas (International wound journal, 2018)
Soft tissue sarcomas occur most commonly in the lower and upper extremities. The standard treatment is limb salvage surgery combined with radiotherapy. Postoperative radiotherapy is associated with wound complications. This systematic review aims to summarise the available evidence and review the literature of the last 10 years regarding postoperative wound complications in patients who had limb salvage surgical excision followed by direct closure vs flap coverage together with postoperative radiotherapy and to define the optimal timeframe for adjuvant radiotherapy after soft tissue sarcomas resection and flap reconstruction. A literature search was performed using PubMed. The following keywords were searched: limb salvage, limb-sparing, flaps, radiation therapy, radiation, irradiation, adjuvant radiotherapy, postoperative radiotherapy, radiation effects, wound healing, surgical wound infection, surgical wound dehiscence, wound healing, soft tissue sarcoma and neoplasms. In total, 1045 papers were retrieved. Thirty-seven articles were finally selected after screening of abstracts and applying dates and language filters and inclusion and exclusion criteria. Plastic surgery provides a vast number of reconstructive flap procedures that are directly linked to decreasing wound complications, especially with the expectant postoperative radiotherapy. This adjuvant radiotherapy is better administered in the first 3-6 weeks after reconstruction to allow timely wound healing and avoid local recurrence.